Penerapan Kurikulum Merdeka pada Pembelajaran Pendidikan Agama Islam - Fauzi, Anis; Salamah, Umi (Tarbiyatuna Kajian Pendidikan Islam, 2026)
This research aims to explain the application of the independent curriculum in PAI learning for class Class X at Vocational School Cordova Banyuwangi. The type of research used in this research is descriptive qualitative. Data collection methods use participant observation, semi-structured interviews and documentation. The research subjects or respondents in the research were PAI subject teachers, class And data analysis includes data collection. data reduction (data reduction), data display (data presentation), conclusion drawing/verification (drawing conclusions). Valuation. In planning learning, educators prepare Learning Outcomes (CP), Learning Achievement Flow (ACP), prepare learning media. In implementing learning, educators have carried out the steps in the independent curriculum learning method. And for evaluation, educators provide a conclusion and assessment of the material that has been studied. The supporting factors are students being more active in thinking, clear budgeting from the regional government to support the implementation of the independent curriculum, good coordination from the regional government, whether district or provincial, with the central government in providing learning and training facilities. The inhibiting factor is the students' low level of interest in literacy. Students must be fully motivated, limited time and lack of supporting teaching and learning infrastructure. The impact is that it is easier for students to learn according to the topic they want and according to the context of the situation, teachers are more flexible in teaching discussion topics, students are better trained in literacy, students are more active in matters collaborate with friends.